Community structure of nudibranchs (Gastropoda) at Coastal Waters of Waleo Village (Mollucas Sea) and Kalasey Village (Manado Bay, Sulawesi Sea) - Purba, Aprillawati; Kusen, Janny D; Mamangkey, N Gustaf F (Graduate Program of Sam Ratulangi University, 2013)
Nudibranchia are mollusks without a shell. They are simultaneous hermaphrodites and are carnivores while some of them are cannibals. Nudibranchia are frequent occupants and foraging on coral reefs. The study was conducted at two locations, namely Waleo Village Waters representing the waters of Mollucas and Sulawesi Sea was represented by Kalasey Village. The difference in the location of the two waters is expected to affect the existence of community structures. The present study includes diversity, richness, evenness, dominance and similarity. A line transect was used to collect data. We found 84 individuals from both study sites representing 8 species of Nudibranchia, which fall into 4 genera and 3 families namely, Pteraeolididae, Phyllidiidae, and Chromodorididae. The most common family was the Phyllidiidae. The similarity value at both locations was 54.5%Â©Â Penelitian tentang struktur komunitas gastropoda nudibranchia telah dilakukan di dua lokasi yaitu Desa Waleo (Laut Maluku) dan Desa Kalasey (Laut Sulawesi). Struktur komunitas yang dikaji meliputi studi keanekaragaman, kekayaan, kemerataan, dominansi dan kesamaan. Metode yang digunakan dalam penelitian adalah line transect. Hasil penelitian menunjukkan, dari kedua lokasi, ditemukan 84 individu yang terdiri dari 8 jenis yang masuk dalam 4 genera dan 3 famili (Pteraeolididae, Phyllidiidae, dan Chromodorididae). Famili Phyllidiidae adalah yang paling umum ditemukan. Nilai kesamaan di kedua lokasi adalah 54,5%Â©